Advantages and importance of natural dyes in the restoration of textile cultural heritage - (:unkn) unknown (Universitatea "Alexandru Ioan Cuza" din Iasi, 2016)
Identification of an art object material of cultural heritage had received significant attention, because of its importance for the development of appropriate restoration and conservation strategies. In this paper, optical microscopy, CIE L*a*b* spectrophotometer/colorimeter, scanning electron microscopy (SEM) coupled to energy dispersive X-ray (EDX) spectroscopy and high performance liquid chromatography coupled to diode-array-detection (HPLC-DAD) are used to investigate many historical textiles samples in some museums.
Keywords: Colour measurements; Cultural heritage; HPLC-DAD; Natural dyes; Restoration; SEM-EDX